Evaluating photosynthetic performance of transgenic soybean harboring CKX13 under salinity conditions - My Duyen, Vo Thi; Lan Xuan, Hoang Thi; Hoang Tu, Tran Nguyen; Tien-Dung, Nguyen; Phuong Thao, Nguyen (Vietnam Journal of Biotechnology, 2023)
Cytokinins (CKs) are considered one of the critical phytohormones with an important role in plant response to abiotic stresses. One of the key enzymes in regulating CK levels is CK oxidase/dehydrogenase (CKX), which catalyzes the irreversible CK degradation. Although CKX gene members in soybean (Glycine max) have been identified, their importance in plant tolerance against salinity has not yet been fully elucidated. In this study, GmCKX13, a gene with upregulated expression in various tissues of soybean at various stages under water deficit condition as shown in previous investigation, was selected for exploring its role in relation to photosynthetic performance under salt stress conditions. The results showed that the transgenic soybean overexpressing GmCKX13 could maintain a better assimilation rate compared to their wild-type (WT) counterparts under the salinity condition. This could be explained by the higher chlorophyll content and the less damage caused by the stress in the photosynthetic machinery of the transgenic plants. According to the analyses, the transformers displayed higher values of maximal photosystem II (PSII) photochemical efficiency (Fv/Fm), maximal quantum yield of primary PSII photochemistry (φPo), quantum yield for electron transport (φEo) and efficiency for electron being transferred from QA- to plastoquinone (ψEo). The evaluation for the overall photosynthetic performance using performance index in absorption basis (PIABS) also supported the differential photosynthesis potential between the two genotypes. Collectively, these findings suggested that appropriate GmCKX13 modulation could enhance photosynthetic adaptation to salt-stressed conditions in soybeans.